Contesting stereotypical representations of the Chinese by Chinese university students - Seng, Hui Zanne (2020)
Stereotypical representations are the generalised descriptions and assumptions made about a group of people, which are constructed, transmitted, and learned through discourse in social interactions. Stereotyping discourse is portrayed as fact that certain characteristics are shared among all the members of the group. Much has been written on the negative consequences of defining people, particularly marginalised groups in stereotypical ways, highlighting discrimination and perpetuation of social inequalities as their result. On the other hand, less work has been done focusing on how the people facing stereotypical traits and behaviours attributed to them deal with or respond to the stereotyping discourses. However, in order to fully understand the effects of stereotyping, it is important to first examine the processes through which targets of stereotyping discourses are able to recognise such discourses as negative and act to remove themselves from the subject positions they are placed in those discourses. This is especially so when the stereotyping discourse is subtle and not easily identified, and hence, more difficult to resist. This study sought to investigate Chinese university students’ response towards stereotypical representations of the Chinese described in an intercultural training video. Specifically, the study examined how the students interpret negative stereotyping discourses in the video and employ strategies to resist stereotypical representations. A video produced by a well-known ‘expert’ teaching intercultural communication with Chinese people was screened to sixteen university students from the People’s Republic of China studying at a Malaysian university. Focus group discussions were conducted with the participants after the video screening to obtain their reactions to the representations of Chinese identity and behaviour described by the intercultural trainer in the video. Analysis of the data was informed by Fairclough’s (2001) three dimensional framework for discourse analysis, van Leeuwen’s representation of social actors (2008) and van Dijk’s ideological square (2011). The findings show that participants were not aware of the discourse context in which stereotyping descriptions are used as the trainer’s resource in his intercultural training business whereby constructing people as “different” from the clients in his training session is a matter of business survival. Also, participants were ambivalent in their recognition of stereotyping discourses and demonstrated difficulty in resisting them. The strategies found employed by participants in resisting what they regarded as negative descriptions of the Chinese were to construct subgroups within the superordinate group, reframing stereotypes as positive, normalising stereotypical traits and behaviours, positioning themselves as outsider, questioning the expertise of the trainer, devaluing the perspectives of the “out-group”, and rationalising the negative representations through philosophising about the fluidity of culture. The study concludes that resisting and removing oneself from stereotypical representations in which one is placed requires intense identity work and is difficult to achieve. This study contributes to the study on empowering victims of stereotyping discourse, sheds light on the difficulty of the members of the stereotyped group to recognise stereotyping discourses and resist the stereotypical representations.